Uji Perbedaan Harga Pokok Produksi Senyatanya dengan Harga Pokok Produksi Ekonomis pada Perusda Es Saripetojo - SUSENO SUSENO; Sri Hartati; siti fatimah (Majalah Imiah Manajemen & Bisnis, 2021)
This study aims to determine the optimal level of production at Perusda Saripetojo Cilacap and the difference between the actual cost of production and the economic cost of production. The analysis in this study uses production cost analysis to determine optimal production and cost of goods, then performs the second hypothesis using the t test and obtained t arithmetic hypothesis 1 (df) = 6, 95 percent confidence level, t table of 2.4469, t count 1.528 and hypothesis 2 with t count 1.034 then both are in the area of rejection of H0 and acceptance of ha. The results in this study indicate that the production level set by Perusda Es Saripetojo is optimal, this can be seen from the results of hypothesis testing which states that there is no significant difference between the level of actual production with an optimal level of production, and the cost of production set by the company Perusda Es Saripetojo is already economical Keywords: Production Cost, Cost Of Production, Optimal Production Level